A DSGE Model of China - Li Dai; Patrick Minford; Peng Zhou (Cardiff University, Cardiff Business School, 2014)
We use available methods for testing macro models to evaluate a model of China over the period from Deng Xiaoping's reforms up until the crisis period. Bayesian ranking methods are heavily influenced by controversial priors on the degree of price/wage rigidity. When the overall models are tested by Likelihood or Indirect Inference methods, the New Keynesian model is rejected in favour of one with a fair-sized competitive product market sector. This model behaves quite a lot more flexibly' than the New Keynesian.
Keywords: C11; C15; C18; E27; 330; China; DSGE; Bayesian Inference; Indirect Inference